THROUGHFALL PADA JABON MERAH (ANTHOCEPHALUS MACROPHYLLUS) - Srida Mitra Ayu; Andi Rosdayanti; Eka Lolita (Universitas Andi Djemma Palopo, 2020)
This study aims to measure the throughfall of Anthocepalus macrophyllu. The research was conducted in the experimental garden of SMK Neg 4 Luwu, Baramamase Village, Walenrang District, Luwu Regency. The materials used were 6 samples of Anthocephalus macrophyllus trees with a device consisting of a manual rainfall gauge, a hose, a collection bucket, a measuring cup, nails, machetes and a stopwatch. The data collected were rainfall and rainfall at 30 rain events. Of the 30 rainfall events, the throughfall data were selected for rainfall of 100, 150, 300, 400 and 500 cm3, each with 3 replications. Rainfall data is obtained by placing a manual rain gauge at the research location to measure every time it rains. Throughfall measurement is done by placing the collection bucket on the inside under the canopy. The highest average throughfall of 42.67 cm3 is found in the 500 cm3 rainfall with the regression equation y = 0.086x + 1.202 and determination (R2) = 0.8099. While the largest proportion of throughfall with a value of 13.05% occurs in 300 cm3 of rainfall, the regression equation y = 0.0022x + 8.186 and determination (RÂ²) = 0.0247